PROBLEMATIKA PENERJEMAHAN ARAB-INDONESIA MAHASISWA PBA SEKOLAH TINGGI AGAMA ISLAM YOGYAKARTA - nuha, ulin (Nahdlatul Lughah, 2024)
For Indonesians, Arabic is a second language, so not all Indonesians understand and master Arabic. Therefore, if necessary, a translation from Arabic to Indonesia needs to be used as a forum for people who do not understand and master Arabic. This means that people are needed who can translate Arabic texts into Indonesian. In the process and steps of translation, various kinds of obstacles and problems must be found. Likewise, PBA STAI Yogyakarta students also experienced problems and obstacles when they tried to translate an Arabic text into Indonesian. Among the problems encountered by PBA STAI Yogyakarta students in the translation effort include linguistic problems that include the realms of morphology, syntax, and semantics. In addition, they also experience non-linguistic problems in the translation effort, namely the problem of the content and material of the text that is different from the translator's educational background and also the problem of conditions when translating a text.